From Thermal Field Theory to Neural Networks: A Day to Remember Tanguy Altherr : Cern 4 November 1994 - Aurenche.P (World Scientific, 1996)
Tanguy Altherr was a Fellow in the Theory Division at CERN, on leave from LAPP (CNRS) Annency. At the time of his accidental death in July 1994, he was only 31. A meeting was organized at CERN, covering the various aspects of his scientific interests: thermal field theory and its applications to hot or dense media, neural networks and its applications to high energy data analysis. Speakers were among his closest collaborators and friends.